2012
DOI: 10.1111/j.1423-0410.2012.01601.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of the ADVIA cerebrospinal fluid assay to count residual red blood cells in blood components

Abstract: The ADVIA CSF assay is a sensitive, precise and accurate means to assess rRBC counts in non-RBC components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
4
7
0
Order By: Relevance
“…While the RBC content of each PC that was transfused during the study period was not quantified, quality control data from the participating centres indicated that the mean RBC content in PCs prepared from whole blood collections or obtained from apheresis devices was only 0·036 and 0·00043 ml, respectively (http://www.bancsang.net/en/professionals/resum_qualitat.html, last accessed 2 June 2014). These data, regarding the RBC content in PCs, are consistent with previous reports (Santana & Dumont, ; Culibrk et al , ). There is evidence that the minimum RBC volume necessary to elicit a primary anti‐D immune response is only 0·03 ml (Lozano & Cid, ), which is within the range of the quality control data from the centres in this study that transfused PCs prepared from whole blood collections.…”
Section: Discussionsupporting
confidence: 93%
“…While the RBC content of each PC that was transfused during the study period was not quantified, quality control data from the participating centres indicated that the mean RBC content in PCs prepared from whole blood collections or obtained from apheresis devices was only 0·036 and 0·00043 ml, respectively (http://www.bancsang.net/en/professionals/resum_qualitat.html, last accessed 2 June 2014). These data, regarding the RBC content in PCs, are consistent with previous reports (Santana & Dumont, ; Culibrk et al , ). There is evidence that the minimum RBC volume necessary to elicit a primary anti‐D immune response is only 0·03 ml (Lozano & Cid, ), which is within the range of the quality control data from the centres in this study that transfused PCs prepared from whole blood collections.…”
Section: Discussionsupporting
confidence: 93%
“…When counting very low levels of cells, misclassification of a few cells may be crucial. Conversely, if major numbers of cells are counted, then a few misclassifications are not of significance, as demonstrated in the study by Culibrk and colleagues, who successfully used the ADVIA 2120 to detect residual RBCs in plasma and platelet concentrates …”
Section: Discussionmentioning
confidence: 99%
“…Interest in the use of hematology analyzers to count rRBCs was renewed by the latest generation of instruments being able to count low levels of cells in body fluids (BFs). Assessment of the cerebrospinal fluid (CSF) analysis mode on an ADVIA 120 hematology analyzer (Siemens, Berlin, Germany) found that although sample predilution was required for counting of rRBCs, the assay met the required performance characteristics 13 …”
Section: Introductionmentioning
confidence: 99%